2010
DOI: 10.1002/ejoc.200901479
|View full text |Cite
|
Sign up to set email alerts
|

Calix[6]arene‐Picolinamide Extractants for Radioactive Waste Treatment: Effect of Additional Carboxy Binding Sites in the Pyridine 6‐Positions on Complexation, Extraction Efficiency and An/Ln Separation

Abstract: Keywords: Calixarenes / Actinides / Lanthanides / Waste treatment / N ligandsThe effect of the presence of an additional ester or amide carboxy group in the 6-position of the pyridine nuclei of calixarene-based picolinamide ligands on the extraction and complexation properties of lanthanide(III) and actinide(III) metal ions was studied. For this purpose, six new ligands 1-6 were synthesized; their conformational properties were studied both in solution and in the solid state, and their binding properties towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…However, it was demonstrated that the addition of the dicarbollide anion strongly improved the extraction efficiency and that it is possible to reach the desired values of D M (metal ion distribution coefficient = [M] org /[M] aq at equilibrium) at the target pH value by varying the dicarbollide concentration. 16,17 It was verified that the enhanced extracting capability of the Calix/Br n CD mixture with respect to calixarene alone was not due to the extracting capability of the synergiser. 16 The experimental conditions for the extraction tests performed on La 3+ aqueous solutions were chosen after some preliminary radioactive extraction experiments.…”
Section: Extraction Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…However, it was demonstrated that the addition of the dicarbollide anion strongly improved the extraction efficiency and that it is possible to reach the desired values of D M (metal ion distribution coefficient = [M] org /[M] aq at equilibrium) at the target pH value by varying the dicarbollide concentration. 16,17 It was verified that the enhanced extracting capability of the Calix/Br n CD mixture with respect to calixarene alone was not due to the extracting capability of the synergiser. 16 The experimental conditions for the extraction tests performed on La 3+ aqueous solutions were chosen after some preliminary radioactive extraction experiments.…”
Section: Extraction Resultsmentioning
confidence: 92%
“…16,17 It was verified that the enhanced extracting capability of the Calix/Br n CD mixture with respect to calixarene alone was not due to the extracting capability of the synergiser. 16 The experimental conditions for the extraction tests performed on La 3+ aqueous solutions were chosen after some preliminary radioactive extraction experiments. Since nitrobenzene was used as a diluent in the preliminary extraction tests for the ESI experiments but no data for 1 in nitrobenzene was available in the literature, the ligand behaviour in this diluent was established.…”
Section: Extraction Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The reaction was realized in a semi-industrial scale unit [24] . A dual envelop reactor of 30 litres capacity was used.…”
Section: General Methodsmentioning
confidence: 99%
“…Thanks to the knowledge acquired within the field of the SNF hydrometallurgical reprocessing [44][45][46][47], we are herein reporting, for the first time, the synthesis and application of the hydrophilic complexant 1,10-phenanthroline-2,9-dicarboxamide, N 2 ,N 9 -bis[1,3dihydroxy-2-(hydroxymethyl)propan-2-yl] (1) (see Figure 1) as Am(III) selective stripping agent in the i-SANEX process. Similarly, the simpler hydrophilic phenanthroline-based ligands PDA (2) and PDALC (3), presenting the same donor set but with different coordinating ability, were tested and compared to 1.…”
Section: Introductionmentioning
confidence: 99%